Myths and legends of ancient Britain and Ireland. - World Book, Inc. (Chicago : World Book, a Scott Fetzer company, 2016)
"Myths and legends from Ancient Britain and Ireland. Features include information about the history and culture behind the myths, pronunciations, lists of deities, word glossary, further information, and index"--Provided by publisher.
Includes bibliographcial references (page63) and index.
Keywords: Mythology, Celtic -- Juvenile literature; Celts -- Folklore -- Juvenile literature; Britons -- Folklore -- Juvenile literature; Scots -- Folklore -- Juvenile literature; Ireland -- Folklore -- Juvenile literature; Wales -- Folklore -- Juvenile literature; Scotland -- Folklore -- Juvenile literature